2014
DOI: 10.1063/1.4890832
|View full text |Cite
|
Sign up to set email alerts
|

The water entry of slender axisymmetric bodies

Abstract: We present a study of the forces, velocities, and trajectories of slender (length/diameter = 10) axisymmetric projectiles using an embedded inertial measurement unit (IMU). Three nose shapes (cone, ogive, and flat) were used. Projectiles were tested at vertical and oblique impact angles with different surface treatments. The trajectory of a half-hydrophobic and half-hydrophilc case impacting vertically was compared to the trajectory of symmetrically coated projectiles impacting the free surface at oblique angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(40 citation statements)
references
References 24 publications
5
31
0
Order By: Relevance
“…Previous literature used cones as an approximation to bird heads [23]. Trends in impact acceleration noted by Bodily et al [9] for projectiles with conical and ogive noses resemble accelerometer results obtained for seabird models in this study.…”
Section: Bird Heads Vs Conessupporting
confidence: 82%
See 2 more Smart Citations
“…Previous literature used cones as an approximation to bird heads [23]. Trends in impact acceleration noted by Bodily et al [9] for projectiles with conical and ogive noses resemble accelerometer results obtained for seabird models in this study.…”
Section: Bird Heads Vs Conessupporting
confidence: 82%
“…This force arises as the impacting body experiences a net upward force upon impact due to the effects of momentum transfer to the liquid, surface tension, viscous drag and pressure forces [7]. Experimental studies of projectiles [3,4,8,9] show that the forces of blunt body water entry can be maximum anywhere between phases 1 and 5. Thus, the forces of the initial stages of impact must be measured in order to make estimates of the dynamic strength for a given structure [10].…”
Section: Canonical Shapesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigate experimentally the dynamics of the jumper underwater and the hydrodynamic causes of injuries in a high dive, by monitoring one male top-level cliff diver, jumping from different heights during his habitual training with high-speed cameras both in air and underwater and with an accelerometer fixed on his body. The final goal of this work is to better understand the physics underlying high cliff diving as inspired by the studies of the water entry of projectiles [9][10][11] and to be able to protect divers by monitoring their dives with embedded sensors or by designing safety gear.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies on spheres and axisymmetric slender bodies have shown that some other parameters like surface properties and spin imparted to the object can have important influence on splash and cavity formation. [5][6][7][8][9] Other than the hydrodynamic features like splash and cavity formation, there is an important structural perspective to the water impact problem. The central ques- tion is what is the pressure experienced by the object at impact; the theoretical value is given by what is known as the "water hammer" pressure expressed as ρ w V 0 c w , where ρ w is the water density, V 0 is the impact velocity, and c w is the speed of sound in water.…”
mentioning
confidence: 99%